Roles de género en el cine peruano. Personajes femeninos en Madeinusa (2006), La teta asustada (2009) y Loxoro (2012) - Barrueta Cuzcano, Julio Darwin (Ñawi, 2024)
This study analyzes the gender roles of female characters portrayed in Peruvian cinema, in comparison to the feminist approach taken in other regions of the world, with the aim of exposing their characteristic features. For this qualitative analysis, the first three films of Claudia Llosa Bueno have been taken as a sample: Madeinusa (2006), La teta asustada (2009) and Loxoro (2012) are taken as a sample. As a general result, it will be noted that there are particularities that are very specific to Peru, according to the customs, memories, bodies, voices and binaristic thoughts that will determine a differentiated representation of the female characters according to their entirely national construction.